Gambaran Pelaksanaan Analisis Kuantitatif Dan Kualitatif Berkas Rekam Medis Rawat Inap di RSUD Harapan dan Doa Kota Bengkulu - Eki; lasmadasari, novi; arifin, ismail (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2022)
Rsud Harapan dan Doa Kota Bengkulu is one of the hospitals that carries out patient services individually and plenary. One of them is patient services, especially in the medical records section. In their implementation in the assembling department, officers who conduct quantitative and qualitative analysis have not been carried out properly. Objective this study aims to find out an overview of the implementation of quantitative and qualitative analysis of inpatient medical record files at Rsud Harapan and Doa Kota Bengkulu. Method this type of research is descriptive quantitative with a cross sectional approach. The subjects of this study were 83 samples of medical record files for the period of June 2022 and the objects of the assembling department medical record officers as many as 4 people. The data used in this study are primary data that are processed univariately. Results: The implementation of quantitative and qualitative analysis of medical record files was only carried out by 3 (50%) procedure items from the 6 procedure items contained in the SOP; The completeness of the medical record file analyzed quantitatively as much as 32 (38.5%) complete and qualitatively analyzed as much as 54 (65%) complete; Medical record officers 100% have an educational background of D3 Medical Records; Medical record officers have good knowledge of 3 (75%) people in the implementation of quantitative and qualitative analysis of medical record